Does the Provocation Maneuvers Increase the Sensitivity of Sensory Nerve Conduction Studies in Diagnosis of Carpal Tunnel Syndrome? - İŞAK, BARIŞ; SÜNTER, GÜLİN; AKYÜZ, GÜLSEREN DERYA; ULUÇ, KAYIHAN; TANRIDAĞ, TÜLİN (GALENOS YAYINCILIK, 2012)
Objective: The aim of this study was to determine the sensitivity of sensory nerve conduction study (NCS) parameters in the diagnosis of carpal tunnel syndrome (CTS) and to explore if the use of provocative maneuvers improves their sensitivity Materials and Methods: In this prospective study, we included 85 consecutive cases (135 hands) that had signs and symptoms of CTS, and 100 control hands. Sensory NCS was performed in the neutral position and then the wrist was placed in flexion and 90 degrees of extension for 1 min. Onset and peak latencies and velocities, negative peak duration and area, and peak amplitude were measured. Results: The most sensitive parameters were onset latency (77%), and onset (72%) and peak velocities (72%) in neutral position. The flexion maneuver did not increase their sensitivity, however, negative peak area (10%) and amplitude (24%) sensitivities were higher in extended position than in neutral position. Conclusion: The most sensitive NCS parameters were onset latency, and onset and peak velocities in neutral position. The extension maneuver was more sensitive than neutral position. Turk J Phys Med Rehab 2012;58:307-71.
Keywords: Carpal tunnel syndrome; parameters; provocation maneuvers; sensory nerve conduction study; WRIST FLEXION